Penyuluhan Tentang Dampak Penggunaan Gadget Bagi Kesehatan Remaja Di SMP Muhammadiyah Tobelo Halmahera Utara - Jumriani; Putri Yayu; Nurbaety; Yati Purnama (Akademi Kebidanan Tahirah Al Baeti Bulukumba, 2024)
Abstract Technology is currently progressing very rapidly and becoming increasingly sophisticated. With the rapid growth of technology, globalization has entered a modern and advanced phase. The modern world requires society to follow developments that are practical, effective and efficient. The existence of gadgets can fulfill the complex and diverse life needs required by society. Starting from children to the elderly, almost everyone has a smartphone or what is often referred to as a gadget. Gadgets are a form of modern communication media. The research results show that gadgets also have a negative impact, society is becoming more individualistic. Gadgets also have an impact on children's emotional development. Dependence on gadgets can have an impact on growth and development. When addicted to gadgets, children or teenagers will limit their ability to communicate and socialize. This community service activity aims to increase teenagers' knowledge about the impact of using gadgets on health. Held on Wednesday 11 September 2024 starting at 10.00-11.30 WIT at Muhammadiyah Tobelo Middle School, North Halmahera Regency using the counseling method, the results of the activity showed that before being given education, most teenagers did not know the impact of using gadgets and after being given education, 80% of teenagers had good knowledge. regarding the impact of using gadgets on health.